Culinary Endorsement Communication Strategy on Instagram Account @taukotembung - Dana Agestri Hasibuan; Muhammad Alfikri (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The aim of the study is to determine how the promotional strategies used by the @taukotembung instagram account in promoting culinary and their effect on increasing culinary sales who have endorsed at @taukotembung. The study was use qualitative study. This study collects primary data through interviews and observations, specifically by interviewing the owner of the @taukotembung account and one business owner who has endorsed @taukotembung. The data from the interviews were then analyzed by reducing the data so that important data could be obtained to complete this research and draw conclusions in order to answer the questions posed in the problem formulation. The interview results show that the strategy used in conducting promotions is consistent with the 4C theory of social media use, namely context, communication, collaboration, and connection. In the context of @taukotembung paying attention to the quality and aesthetics of their photos or videos and using captions by providing detailed information, communication @taukotembung applies smart reviews or honest reviews when reviewing products or culinary delights, collaboration admin @taukotembung frequently interacts with followers by replying to comments on posts, and finally on the @taukotembung connection, it becomes an ongoing relationship by regularly updating Culinary business owners have increased their sales, according to the results of interviews with business owners who have endorsed with @taukotembung.